New cost calculation method for finding shortest path of hybrid VANET protocol - Phongsathorn Boonnithiphat (2018)
© 2016 IEEE. A Vehicular Ad-Hoc Network (VANET) which enables vehicles to communicate one another has played an important role in the wireless network communication and in the Internet of Things (IoT). Many protocols and standards have been proposed in order to implement VANET. On the road, there are both buses and cars as vehicles. Some protocols uses only cars and some protocol uses only buses for packet forwarding. Hybrid-VANET protocol that uses both buses and cars was proposed However, there are still some challenge in cost calculation for finding the shortest paths from sources to destinations of packets. In this paper, we propose a new method of cost calculation for using in Hybrid-VANET protocol. Our proposed method is more effective in the term of packet losses and computing complication. We evaluate our proposed method by simulation. The experimental results show that our method improves the packet losses and packet delays over Hybrid-VANT and some other VANET protocols.